A Flexible Multi-Rate Allocation Scheme for Balanced Multiple Description Coding Applications - Tillo, T.; Baccaglini, E.; Olmo, G. (2005 IEEE 7th Workshop on Multimedia Signal Processing, 2005)
When transmitting multimedia information over non-prioritized networks subject to packet losses, multiple description coding with an arbitrary number of descriptions is an effective choice in order to minimize the end-to-end distortion. Such descriptions should be generated so that the quality obtained decoding a subset of them depends only on their number and not on the particular received subset. In this paper, we propose an encoding procedure to generate an arbitrary number of balanced descriptions using a multi-rate allocation scheme which exploits the R-D characteristic of the data